CONHECENDO A REDE COMPLEMENTAR DO SUS: ASSISTÊNCIA À SAÚDE AOS PRIVADOS DE LIBERDADE - Anjos, Alyne B.; Brandão, Amanda A.; Guedes, Bianca L.; Silva, Daiane B. da; Lana, Diana Débora Pereira de; Sousa, Luisa Paula de A.; Marques, Sabrina P.; Chaves, Monica (Sinapse Múltipla, 2020)